(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research is motivated by the need to improve operational efficiency and service quality at Ella Digital Printing, which still faces obstacles in the form of unstructured workflows, overlapping employee tasks, and the absence of standard service procedures. This research aims to develop a Service Blueprint as an effort to improve operational efficiency and customer satisfaction at Ella Digital Printing. This research uses the Research and Development (R&D) method with stages of analysis, design, development, implementation, and evaluation. The analysis stage is carried out through observation, interviews, and questionnaires to identify problems and service needs. The design stage produces a Service Blueprint and service SOP which are then validated by management experts, work system design experts, and practitioners with a very feasible category. The implementation results show that the Service Blueprint can be implemented well even though it requires initial adaptation from employees. Evaluation through customer questionnaires shows an increase in operational efficiency and customer satisfaction, especially in aspects of service speed, clarity of process flow, and print quality. This study concludes that the development of the Service Blueprint is effective as a business development approach to improve operational efficiency and customer satisfaction at Ella Digital Printing. This research is recommended to be further developed on a wider business object and scale to obtain more comprehensive results.